Pengaruh Self Management Terhadap Kepatuhan Memodifikasi Gaya Hidup Pada Penderita Hipertensi: Self Management, Kepatuhan Memodifikasi Gaya Hidup, Hipertensi - abdillah, alvin (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2022)
The increasing prevalence of hypertension in the community is caused by a lack of desire to change attitudes and behavior in modifying a healthier lifestyle. Interventions that can be done in changing one's attitudes, behavior and beliefs are self-management. Self-management is a procedure to regulate and encourage a person to use resources in managing his illness. This study aims to determine the effect of self-management on adherence to modifying the lifestyle of patients with hypertension. Methods: The design of this study used a non-equivalent control group with 30 respondents, the sample was taken by simple random sampling. Results. The results of this study indicate that there is an effect of self-management on adherence to lifestyle modification in the intervention group with a significant value, namely p=0.028 (p<0.05). Conclusion: There is an effect of self-management on compliance with modifying the lifestyle of hypertension sufferers in Wanasaba Public Health Center, Lombok Timur